Chromium-catalyzed migratory arylmagnesiation of unactivated alkynes. Issue 10 (11th July 2017) - Yan, Jianming; Yoshikai, Naohiko
Abstract : The first example of 1, 4-chromium migration was observed in the addition of an aryl Grignard reagent to an unactivated alkyne. Abstract : We report here on a chromium-catalyzed addition reaction of an arylmagnesium bromide to an unactivated internal alkyne to afford an ortho -alkenylarylmagnesium bromide. This reaction likely proceeds via the insertion of an alkyne into an arylchromium species, alkenyl-to-aryl 1, 4-chromium migration, and transmetalation between the resulting arylchromium species and the starting aryl Grignard reagent. The product of this reaction is amenable to a series of electrophilic trapping reactions.